DEVELOPMENT OF RURAL MANUFACTURING SME CLUSTERS IN A DEVELOPING COUNTRY: THE INDONESIAN CASE - Tulus Tambunan (2008)
Development of manufacturing small and medium enterprises (SMEs) is a key engine to promote development of rural economy in developing countries. A common industrial organization among manufacturing SMEs, especially in rural areas, in Indonesia as in many other developing countries is clustering, where firms producing similar products concentrate in a certain area. This has led the Indonesian government to adopt a clustering approach as an important element in its rural development strategy to promote the development of rural industry, which consists mainly of SMEs. The main aim of this study is to identify critical success factors of development of rural manufacturing SME clusters in Indonesia. From a number of cases, it reveals that direct government supports are not the main successful factor, or the role is minimal. Instead, the most critical ones are strong inter-firms linkages in clusters and external networks between the clusters and institutions outside the clusters, especially large enterprises (LEs), through subcontracting and traders/trading companies in urban areas. Through such external linkages, firms in clusters secure their access to a wider market.
Keywords: SME; SME Cluster; rural economy; soccess factors; Tegal metalworking industry; SME; SME Cluster; rural economy; soccess factors; Tegal metalworking industry